Pengaruh Word of Mouth (WOM) dan Harga Terhadap Keputusan Pembelian Ayam Goreng Pak Kuwadi - Noviadry Nur Tamtama; Humairoh Al Hakim; Dea Putri Puspitaningrum; Belinda Jihan Fadilah Anindita (eCo-Fin, 2025)
Micro, Small, and Medium Enterprises (MSMEs) continue to grow rapidly in Indonesia, where Word of mouth (WOM) and pricing factors play an important role in influencing consumer purchasing decisions. In the culinary industry, WOM is considered a more credible source of information compared to advertising because it comes from the experiences of customers who have directly tried the product. Meanwhile, competitive pricing becomes an essential factor in purchasing decisions, especially in the food industry, which is highly sensitive to price changes. This study aims to analyse the influence of WOM and pricing on purchasing decisions at the Ayam Goreng Pak Kuwadi business in Klaten. Using a quantitative approach, this study involved 30 respondents selected through purposive sampling. The results show that both WOM and pricing have a positive and significant influence on consumer purchasing decisions. Based on these results, it is recommended that business owners optimize their WOM strategies by creating positive customer experiences and implementing pricing policies that match the product quality to improve customer satisfaction and loyalty. This study provides practical guidance for culinary business owners in developing more effective marketing strategies to strengthen their competitiveness in the market.